Epidemiological Dynamics of Extended-Spectrum β-Lactamase- or AmpC β-Lactamase-Producing Escherichia coli Screened in Apparently Healthy Chickens in Uganda - Steven Kakooza; Damien Munyiirwa; Paul Ssajjakambwe; Edrine Kayaga; Dickson Stuart Tayebwa; Dickson Ndoboli; Loreen Basemera; Esther Nabatta; Maria Agnes Tumwebaze; John Baligwamunsi Kaneene (Scientifica)
The dynamics of extended-spectrum β-lactamase- (ESBL-) and AmpC β-lactamase-producing bacteria (which are deadly groups of antimicrobial-resistant bacteria) have not been well understood in developing countries. This raises major concerns to antimicrobial resistance (AMR) control. We investigated the prevalence and factors linked to the fecal carriage of ESBL- or AmpC-producing Escherichia coli (ESBL-/AmpC-EC) in commercial chickens. Cloacal swabs from 400 birds were sampled and submitted to the Central Diagnostic Laboratory for ESBL-/AmpC-EC screening by culture methods using MacConkey agar supplemented with cefotaxime. Epidemiological data were collected using a structured questionnaire and plausible risk factor analyses prepared by R software using X2 test and logistic regression modeling. Results showed that the prevalence of ESBL-/AmpC-EC was 17.5%. Univariable screening hypothesized that carriage was probably influenced by a type of commercial chicken, geographical location, age group, flock size, and housing system (p<0.05). Modeling exposed that broiler birds were at a higher risk of being ESBL-/AmpC-EC carriers (COR = 9.82, CI = 3.85–25.07). Birds from Wakiso Town Council (COR = 4.89, CI = 2.04–11.72) and flocks of 700–1200 birds were also at a higher risk of harboring ESBL-/AmpC-EC (COR = 2.41, CI = 1.11–5.23). Birds aged 4 months and below were more susceptible to ESBL-/AmpC-EC carriage compared with those aged 1 month and below being 6.33 times (CI = 1.65–24.35) likely to be carriers. The occurrence of ESBL-/AmpC-EC in flocks suggests possible treatment failures while managing colibacillosis. Consequently, injudicious antimicrobial use should be replaced with an accurate diagnosis by bacterial culture and sensitivity testing so as to circumvent AMR emergence, spread, and associated losses.